2011
DOI: 10.1620/tjem.223.125
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Stereotactic Radiosurgery in the Management of Brain Metastases from Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is characterized by brain metastases that occur in about 30 to 50% of patients. To control tumor growth potential with maintaining neurocognitive function is important in the recent radiotherapy against brain metastases. From this viewpoint, we investigated the utility of repeat stereotactic radiosurgery (SRS) with a linear accelerator in the management of brain metastases from NSCLC. Between October 1998 and May 2010, 28 patients harboring brain metastases received repeat SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…One of the advantages of SRS is that the procedure can be repeated for both recurrent and new metastases with more meaningful feasibility, effectiveness, and safety than other treatment modalities [ 6 ]. However, only a few papers have reported on repeat SRS for recurrent metastasis following earlier SRS [ 1 , 3 , 6 , 8 - 11 , 14 ], and moreover, they focused on the results of the repeat SRS itself and the targeted brain metastases included both locally recurring and newly developed tumors after the first SRS, which are clearly pathophysiologically different.…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of SRS is that the procedure can be repeated for both recurrent and new metastases with more meaningful feasibility, effectiveness, and safety than other treatment modalities [ 6 ]. However, only a few papers have reported on repeat SRS for recurrent metastasis following earlier SRS [ 1 , 3 , 6 , 8 - 11 , 14 ], and moreover, they focused on the results of the repeat SRS itself and the targeted brain metastases included both locally recurring and newly developed tumors after the first SRS, which are clearly pathophysiologically different.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are five known cases series presenting the clinical outcomes of rSRS for recurrent distant brain metastatic disease after prior SRS, with only three of the studies presenting overall survival from time of rSRS. Chen et al, Kwon et al, and Mariya et al presented median survivals from rSRS of 6.5, 7.3, and 11 months, respectively ( 18 20 ). Though the median survival reported from all of the studies from initial SRS was somewhat broader in range of 11.5–26 months ( 18 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a study by Kwon et al , 43 patients underwent salvage SRS and the median survival from the time of SRS for recurrent/progressive disease was 8 months (13). More recently, Mariya et al reported that repeat SRS is an effective treatment option, leading to a long survival with a decreased neurological decline (14,15). The authors analyzed 28 patients who underwent salvage radiosurgery for recurrent brain metastases from NSCLC showing a median survival from initial SRS of 26 months and 11 months for post-repeat SRS.…”
Section: Discussionmentioning
confidence: 99%